Telaah Faktor Risiko dan Pemeriksaan Osteoartritis terhadap Kualitas Hidup Masyarakat Desa Kendalpayak Malang: Study of Risk Factors and Examination of Osteoarthritis on the Quality of Life of Kendalpayak Village Malang - Winarsih, Sri; Achmad, Anisyah; Huwae, Thomas Erwin Christian Junus; Hariyanti, Tita; Septiana, Celsy Citra; Palastri, Aisha Rifda; Purwati, Ajeng Budi; Frista, Ardaleni; Rahmani, Nuraida Fara (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Osteoarthritis is a degenerative disease characterized by loss of synovial fluid and articular cartilage in the joints, causing pain and difficulty moving which harms people's quality of life. This community service activity aims to examine the risk factors and results of osteoarthritis examinations on the quality of life of the community. The activity was carried out by collecting data on risk factors and quality of life of the community from 10 elderly integrated health service centers in Kendalpayak. Osteoarthritis examination is carried out based on a clinical examination by a Bone Specialist at Saiful Anwar Hospital. The results obtained were 94 women and 19 men, aged 40-45 years 12 people, 46-60 years 43 people, and 54 people aged >60 years. The Body Mass Index categories of underweight, normal, overweight, and obesity were 4.4%; 45.1%; 30.1%; and 20.4%, respectively. Menopause status ≤10 and >10 years were 22.3% and 29.9%. The data collection on light, moderate, and heavy exercise patterns were 68.2%; 27.4%; 4.4%. The physical activity data collected from light, moderate, and heavy respectively were as follows: 39%; 52.2%; 8.8%. There were 5.3% who had a history of bone trauma. Based on clinical examination, 7.2% were positive for osteoarthritis. Measuring quality of life using the EQ-5D questionnaire in osteoarthritis sufferers shows the severity of the dimensions Mobility (56.1%), Self-Care (24.2%), Usual Activities (41.5%), Pain/Discomfort (92.7%), and Anxiety/Depression (61%). In conclusion, risk factors that influence the quality of life of osteoarthritis sufferers in Kendalpayak Village, Malang include being elderly, female, and menopausal.